(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article will present a study of democracy, analyzing democratic control as a tool to make the exercise of the elective mandate more responsible and responsive. In this vein, the features of accountability and its reflexes in political representation will be examined, its dimensions and forms of expression – social, popular and institutional –, addressing the sufficient features to its expression in democracies. Finally, it will be outlined the democratic model embodied in the Federal Constitution of 1988 and how the intertwining of forms of control, notably the institutional, with the scope of verifying whether the Brazilian representative democracy presents weaknesses regarding the observance of popular desires.